Youth soccer team`s match dynamics with and without the ball when in both conditions of advantage and disadvantage - Kunrath, C. A.; Bedo, B. L. S.; Aquino, R.; Laporta, L.; De Conti Teixeira Costa, G.; Araújo, D.; Leonardi, T. (International Journal of Performance Analysis in Sport, 2025)
The aim of this study was twofold: i) to compare the collective organisation and running performance with and without the ball, in conditions of advantage and disadvantage; ii) characterise and analyse the methods of attack and defence prevalent in the team during these conditions. Considering two play-off matches of a youth team, 150 actions with and 166 without the ball it was analysed. The dependent variables were captured by GPS devices, while the attack/defence method prioritised by the team was identified through notational analysis. The team prioritised positional attack and mixed defence at a disadvantage, and direct attack and zone defence at an advantage in the clashes. With the ball and at a disadvantage, the team occupied a greater surface area and width, covered a greater distance at low intensity and displayed more accelerations. Without the ball and at a disadvantage, the team also occupied a greater surface area, in width and length, remaining less compacted. The team also showed less physical effort at a disadvantage. We conclude that the team differed in collective organisation, method of attack and defence and running performance both with and without the ball, considering whether it had an advantage in the clashes.